Production of biosurfactant by Bacillus subtilis RSL-2 isolated from sludge and biosurfactant mediated degradation of oil. (July 2020) - Sharma, Swati; Pandey, Lalit M.
Graphical abstract: Highlights: B. subtilis RSL-2 resulted crude oil-degrading & biosurfactant producing properties. Culture conditions were optimized for lipopeptide production using Response Surface Methodology. Produced lipopeptide improved surface wettability i.e. increased surface energy. Biosurfactant co-feeding improved oil bioavailability and cell surface hydrophobicity. This strategy resulted 1.6 folds higher oil degradation and biosurfactant production. Abstract: This study aims to unveil the effect of biosurfactant as stimulant in crude oil bioremediation. Isolated oil-degrading strain, B. subtilis RSL 2 was optimized for the maximum oil degradation and biosurfactant production using Response surface methodology. The produced biosurfactant was characterized and investigated for its effect on microbial oil degradation in two modes (a) sequential and (b) simultaneous. The strain produced 3.5 g/L of biosurfactant at pH 4.0, 25 °C, using 1 g/L crude oil as the only C-source in 7 days, which was characterized as lipopeptide with a critical micelle concentration (CMC) of 0.5 g/L. The biosurfactant improved surface wettability of a hydrophobic substrate i.e. increased surface energy from 30 ± 1 to 35 ± 1 mJ/m 2 . Further, the simultaneous feed of biosurfactant at 0.5 CMC enhanced oil biodegradation (72%) and biosurfactant production (5.2 g/L) by about 1.6 times than the sequential mode due to improvement in mobilization of oil thus making it more bioavailable.